THE AMBIVALENCE OF GENDER TRANSGRESSION IN DANGAL FILM (2016) - Ripki, Mochamad; Rahayu, , Lina Meilinawati; Adipurwawidjana, Ari Jogaiswara (Universitas Pakuan, 2024)
ABSTRACTThis research aims to analyze how the Dangal film displays gender transgression towards gender construction in the sport of wrestling carried out by the Phogat family. By focusing on scenes and dialogue in the Dangal film, this research is analyzed using film narratology which is elaborated on Judith Butler's ideas regarding gender performativity and Sandra Harding's ideas regarding the gender construction process. The results of this research reveal that in the Dangal film, there is gender transgression that is shown not only focused on the physical appearance dimension but also on the conceptual and symbolic dimensions of ideas. However, instead of presenting gender transgression as an act of transcending gender norms that discriminate against women, Dangal ambivalently opposes patriarchal hegemony by not embracing the femininity of the female characters, namely Geeta and Babita, which is carried out through acts of defeminization of their character development.Keywords: Gender transgression; Gender construction; Defeminization